KONSEP TA’WIL USHULIYYIN DAN RELEVANSINYA DENGAN PEMBAHARUAN HUKUM ISLAM - Syahrial Dedi (JURIS (Jurnal Ilmiah Syariah), 2018)
The experts of the Islamic law methodology (Ushuliyyin) have inherited the ta'wil method; a method of discovering the esoteric meaning in the textual disclosure.  The application of ta'wil method must be exactly based on predetermined rules of play. The mistake of understanding a method will have negative impact toward the law product. This phenomena was worried about by the ushuliyyin very much. This research is a library study with content analysis method. This study concludes that ta'wil according to ushuliyyin that is, the abrogation of a pronouncement of the meaning of zhahir to another meaning which is not quickly captured, because there is a proposition that the meaning is meant by the pronouncement. Evidence of ta'wil in the form of nash, qiyas, luhgawiyyah, 'aqliyyah, and' adad ('urf), and the argument disputed is the wisdom of al-tasyri' (maqashid al-syari'ah) which is practiced only by ulama ushul al-Hanafiyyah. Ta'wil covers the furu' problems. Ushuliyyin finds some form of ta'wil, among which specializes in general pronouncing (takhshish al-'am), limiting the mutlaq (taqyyid al-mutlaq), transfer the utterance from the essential meaning to the majazi, or from the obligatory meaning of the sunnah. Generally the ta'wil method is still considered relevant to the renewal of Islamic law.